2020
DOI: 10.1136/bmjsem-2020-000752
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in baseline neurocognitive testing for student concussion management in Massachusetts high schools

Abstract: PurposeThere is evidence of socioeconomic disparities with respect to the implementation of student-sports concussion laws nationally. The purpose of this study was to examine school sociodemographic characteristics associated with the provision of computerised baseline neurocognitive testing (BNT) in Massachusetts (MA) high schools, and to assess whether the scope of testing is associated with the economic status of student populations in MA.MethodsA cross-sectional secondary analysis of surveys conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Racial disparities have been documented along the spectrum of clinical care; however, representation of Black people or other minoritized groups is often missing in published SRC studies making this difficult to discern. Although previous research demonstrates disparities in access to ATs, 10 accessible baseline neurocognitive testing, 26 use of subspecialty concussion care, 19 and concussion symptom knowledge, 9 understanding care paths between groups can help to answer questions regarding recovery timelines and treatment pathways. Research by Bretzin and colleagues 27 showed that the median time to medical clearance after a SRC varied by healthcare provider and medical facility.…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities have been documented along the spectrum of clinical care; however, representation of Black people or other minoritized groups is often missing in published SRC studies making this difficult to discern. Although previous research demonstrates disparities in access to ATs, 10 accessible baseline neurocognitive testing, 26 use of subspecialty concussion care, 19 and concussion symptom knowledge, 9 understanding care paths between groups can help to answer questions regarding recovery timelines and treatment pathways. Research by Bretzin and colleagues 27 showed that the median time to medical clearance after a SRC varied by healthcare provider and medical facility.…”
Section: Discussionmentioning
confidence: 99%
“…One of the states that included the baseline neurocognitive test in the concussion law is Massachusetts (Doucette et al, 2016) [7] . According to Campbell et al, (2020) [3] , Massachusetts requires all schools to be resourceful enough to purchase a baseline neurocognitive testing program. Also, the qualified personnel who administer the test must have administration experience.…”
Section: Baseline Neurocognitive Testmentioning
confidence: 99%
“…Among high school athletes, Black athletes have also been reported to be less knowledgeable about concussion signs and symptoms than White athletes, 16 which may prevent them from seeking assessment and care. Improving access to education and health care resources for all populations may lead to more equitable care and outcomes in concussion management 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Improving access to education and health care resources for all populations may lead to more equitable care and outcomes in concussion management. 16,17 Outcomes of concussion vary and range from full, rapid recovery to chronic neurologic dysfunction and other sequelae. 7 In children and adolescents, sportsrelated concussions have repeatedly demonstrated significant impacts on academic performance.…”
Section: Introductionmentioning
confidence: 99%